Effect of Green Supply Chain Innovation Alliance on Performance of Manufacturing Firms in Nairobi County - Ngatuny, Julius; Karani, Antony; Namusonge, Eric; Omwenga, Jane (International Journal of Supply Chain Management, 2024)
Purpose: The general objective of the study was to determine influence of green supply chain innovation alliances on performance of manufacturing firms, in Nairobi County Kenya. Methodology: The study was informed by Social Exchange Theory, Transaction Cost Theory, Resource-Based view and Resource Dependency Theory. The research design for this study was an explanatory survey research design; this is primarily a positivism approach. The population for the study will constitute manufacturing firms in Kenya. Thus, the unit of observation was 516 procurement managements from 516 manufacturing firms. The research employed stratified and simple random to select a sample of 225. This study used structured questionnaires to collect data relevant to the study. Descriptive analysis such as means, standard deviation and variance. Findings: linear regression models showed that green supply chain innovation alliances have a positive and statistically significant influence on firm performance, highlighting their essential role in enhancing success for manufacturing firms. A strong partnership with suppliers and specialized expertise in green supply chain management are crucial for this improvement. Unique Contribution to Theory, Practice and Policy: Therefore, the study recommends that organizations actively strengthen their green supply chain innovation alliances by establishing joint sustainability initiatives and creating regular collaboration forums with suppliers to share best practices and innovative solutions.